EKSISTENSI HUKUMAN HUKUMAN CAMBUK PADA PENEGAKAN SYARIAT ISLAM ACEH PASCA PANDEMI COVID-19 - Zuriah Zuriah; Teuku Amnar Saputra (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
Abstract The Covid-19 pandemic is occurring worldwide and is one of the most massive pandemics in history. All regions in Indonesia face this problem including Aceh. The execution of the Cambuk Punishment experienced a long debate and Aceh entered the era of the Covid-19 pandemic. The existence of the execution of cambuk punishment in the field in Aceh is starting to disappear. The Indonesian government started enforcing PPKM and limiting crowds. Based on this background, this study tries to analyze the existence of cambuk in the application of Aceh's Islamic Shari'a after the Covid-19 pandemic. This research was conducted using a sociological approach (Sociological Approach). This sociological approach is used to examine the existence of the implementation of cambuk in the application of Aceh's Islamic Shari'a after the Covid-19 pandemic. This is related to the culture and situation of the people of Aceh which are increasingly changing and continue to experience development from time to time. The results of this study indicate that: The existence of cambuk as a punishment during and after Covid-19 can be seen from the achievement of the goals of punishment by using cambuk, namely that it is seen that the recedive rate or repetition of crimes for convicts who underwent cambuk execution in Aceh was very successful, especially in the pandemic era who are vulnerable to crime. Indicators of this success can also be seen in the reduced spike in cases and repetition of crimes committed by former cambuk convicts. If we look back, this situation is in stark contrast when compared to those convicted of imprisonment or fines when the country is experiencing a pandemic such as Covid-19. Cambuk punisment is a new step to reduce the transmission rate of Covid-19 and cut Aceh's budget during the last Covid-19 pandemic era. Keywords: Cambuk, Aceh, Post Pandemic Covid-19.